Just fly away - McCarthy, Andrew, 1962- (Algonquin, 2017)
Fifteen-year-old Lucy Willows discovers that her father has a son from a brief affair, an eight-year-old boy who lives in the same New Jersey town. She begins to question everything she thought she knew about her family and life, and begins to withdraw from her friends and family. It isn't until Lucy is In Maine to visit her estranged grandfather that she begins to get to the bottom of her family's secrets and lies.